Pengaruh Leverage Dan Likuiditas Terhadap Profitabilitas Pada Perusahaan Yang Terdaftar Di Jakarta Islamic Index Periode 2014-2018 - Bagus Firmansyah; Efi Syarifuddin; Budi Sudrajat (Sains: Jurnal Manajemen dan Bisnis, 2022)
This study aims to examine the effect of liquidity ratios and leverage ratios on profitability ratios, either partially or jointly. The research was conducted on companies listed on the Jakarta Islamic Index (JII) for the 2014-2018 period. Involving 60 companies as the population, while the research sample is 12 companies which are determined based on purposive sampling technique. Data analysis used multiple linear regression, classical assumption test, and hypothesis test. The results showed that liquidity and leverage partially had a significant negative effect on profitability. Simultaneously, liquidity and leverage have a significant negative effect on profitability.